The Level of Success In English For Two and Semester Islamic Education Management Three Students In This Classroom - Lubis, Yani; Pratiwi, Inda; Rambe, Yasmin Azura; Lukman, Paidi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Learning English is intended to facilitate communication between individuals and nations. Proficient use of English enables people to effectively express their ideas, emotions, and thoughts. However, students often struggle with English due to a lack of confidence in using the language in conversational contexts. Utilizing a conversation-based learning model can boost students' confidence in communication, especially when supported by digital modules. This method was tested with a sample of vocational high school (SMA) students. The research involved creating digital teaching materials using the Sigil application, which can be accessed on computers, tablets, and smartphones, and compiling various resources for self-study to enhance conversational skills. The study found that learning through the conversation model resulted in an 81.8% success rate across seven evaluation components.